A study of printability and flash light sintering characteristics with Cu micro/Ag nano hybrid-ink for multi-layered printed circuit board based on printed electronics technique - Chu, Ji Hyeon (한양대학교, 2019)
In this work, the printing and sintering characteristics of pattern area and via-hole section were investigated. To analyze the printing characteristics based on the rheology of ink, Cu micro/Ag nano hybrid-inks (Cu/Ag hybrid-inks) were prepared by varying the epoxy content, and the fabricated inks were printed on via-hole formed substrates. The printed Cu/Ag hybrid-ink films were subsequently sintered by flash light sintering method. Various flash light sintering parameters including irradiation energy and pulse number were employed to enhance the sintering characteristics of pattern area and via-hole section. The sintered Cu/Ag hybrid-ink films were characterized using scanning electron microscopy (SEM) and X-ray photoelectron spectroscopy (XPS). The detailed sintering mechanism of Cu/Ag hybrid-ink inside the via-hole section was monitored in real-time by in-situ resistance monitoring. As a result, the Cu/Ag hybrid-ink with the optimal ratio of epoxy content (0.56 wt%) showed good printability of pattern area and via-hole section. In addition, the proposed multi-pulse flash light sintering conditions (irradiation energy: 7 J/cm2, pulse duration: 1 ms, off-time: 9 ms, pulse number: 20) exhibited low resistivity (pattern area: 5.12 μΩ·cm, via-hole section: 7.79 μΩ·cm) and a 5B adhesion strength level.